The Circumstantial Relational Process Clauses in Scientific Texts in the Framework of SFL - Mulyati Khorina (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2018)
This paper will present the results of the study of circumstantial relational process clauses in scientific texts, especially in mechanical engineering ones. This study is aimed to identify the relational process occurring in Circumstantial relational process clauses and analyze the lexical verbs realizing the relational processes. To conduct the study, three mechanical engineering textbooks used as references by Mechanical Engineering Students of Politeknik Negeri Bandung (Polban) were used as the source for collecting the data. The method used in this study was qualitative one and Systemic Functional Linguistics (SFL) framework was applied to analyze the data. The results showed attributive relational process occur more frequently than identifying one. The attributive relational process was realized by various lexical verbs. The account of this will be presented in the rest of the his paper. Key words: Systemic Functional Linguistics (SFL), circumstantial clauses, function, structure, identifying process, attributive process